2012
DOI: 10.1371/journal.pone.0041207
|View full text |Cite
|
Sign up to set email alerts
|

Highly Dynamic Microtubules Improve the Effectiveness of Early Stages of Human Influenza A/NWS/33 Virus Infection in LLC-MK2 Cells

Abstract: BackgroundThis study aims to investigate the role of microtubule dynamics in the initiation of NWS/33 human influenza A (NWS) virus infection in MDCK and LLC-MK2 mammalian kidney cells. We previously demonstrated a host-dependent role of the actin cytoskeleton in inducing restriction during the early phases of NWS infection. Furthermore, we showed the differential infectious entry of NWS virus in the above mentioned cell models.Methodology/Principal FindingsBy first employing a panel of microtubule-modulators,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 64 publications
(78 reference statements)
2
6
0
Order By: Relevance
“…Similar results demonstrating the limited effect of nocodazole treatment on IAV virion production in MDCK cells are shown in Fig. 4A and have also been reported previously (44). Given the lack of requirement for microtubules and sensitivity to paclitaxel, the formation of these connections may be enhanced as a downstream signaling response to a loss of microtubules during IAV infection.…”
Section: Discussionsupporting
confidence: 90%
“…Similar results demonstrating the limited effect of nocodazole treatment on IAV virion production in MDCK cells are shown in Fig. 4A and have also been reported previously (44). Given the lack of requirement for microtubules and sensitivity to paclitaxel, the formation of these connections may be enhanced as a downstream signaling response to a loss of microtubules during IAV infection.…”
Section: Discussionsupporting
confidence: 90%
“…The discrepancies in the role of F-actin in HA-M2 association between the two above-mentioned studies might be due to differences in the cell types used in these studies (Chinese Hamster Ovary cells in [151] versus primary human blood derived macrophages in [104]). Cell-type dependent differences for the role of the F-actin and microtubules at different stages of the IAV life cycle have also been reported before [94,98,101,179,180,181]. In addition, technical differences could account for the discrepancies; for example, the presence of other viral components in infection-based experiments [104] or attachment of fluorescent proteins to the cytoplasmic domains of HA and M2 in the FRET study [151] may affect the interaction with subcortical actin.…”
Section: Roles Played By the Cytoskeleton At Specific Steps Of Iavsupporting
confidence: 63%
“…Cofilin-1 [89] and cortactin [90], which can promote the disassembly and assembly of F-actin, respectively, are both thought to play positive roles during IAV infection. With respect to microtubules, the disruption of microtubules has no [99] to a moderately negative [39,100] effect on virus propagation, whereas a reduction in efficiency of microtubule assembly increases virus titers in a rhesus monkey kidney cell line [101]. In addition, an increase in tubulin acetylation status, which promotes microtubule function in trafficking [102], was observed to correlate with an increase in virus titers in one study [103], but not in the other [99].…”
Section: Relationships Between Virus Growth and Cytoskeletonmentioning
confidence: 99%
See 1 more Smart Citation
“…With the aim of visualizing viruses along the endosomal trafficking pathway, synchronized infection was established as an important tool that allows monitoring early infection events (Matlin et al , 1981). It has been demonstrated that endosomal trafficking of the virus involves actin- and microtubule-dependent processes (Nielsen et al , 1999; Sun & Whittaker, 2007; De Conto et al , 2012). Using single virus trajectories from imaging fluorescently labelled virions, viral transport was dissected into three different stages (Lakadamyali et al , 2003).…”
Section: Endosomal Trafficking Of Iavmentioning
confidence: 99%